Kontribusi Daya Ledak Otot Tungkai Dengan Kemampuan Long Passing Club Sepak Bola SM Musirawas - Muhammad Supriyadi; Muhammad Suhdy (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2022)
The research objective is to determine how far a variable relates to other variables. The population in this study were SM Musirawas Club football players. Sampling was conducted using a purposive sampling technique: players aged 17-19 years, as many as 25 people. To obtain research data, a vertical jump test was used to measure leg muscle explosive power and an extended kick test to measure long passing. The data obtained were analyzed using the Product Moment formula to determine the contribution determined by the determinant coefficient. The results of the analysis obtained the correlation coefficient rcount = 0.44> rtable = 0.396 (research hypothesis accepted) and tested the effect of the correlation got 2.46 > ttable = 1.71 (significant). In conclusion, there is a substantial relationship between the explosive power of the leg muscles and the long passing ability of Club SM Musirawas football players; there is a contribution between the variable explosive power of the leg muscles to the extended passing knowledge of 19.5%. Keywords: Explosive Power, Limb Muscle, and Long Passing Ability